KEANEKARAGAMAN JENIS BURUNG DI KAWASAN MANGROVE GILI SULAT LOMBOK TIMUR - Gito Hadiprayitno; Agil Al Idrus; M. Liwa Ilhamdi; I Gde Mertha (Universitas Sebelas Maret, 2014)
Abstract- Mangrove at Gili Sulat is the important ecosystems that support the lives of many wildlife species, one of which is species of birds. Birds use the mangroves as searching of food, playing, searching for mates, and nesting. The aim of the research is to determine the diversity of birds species in the mangrove area at Gili Sulat East Lombok. The study was conducted by observations species of birds through surveys (direct observation) using binoculars and use the boat (during water conditions high tide). The result of this research have found nine species of birds, consisting of four species of water birds (Actitis hypoleucos, Butorides striatus, Chlidonias hibridus, and Egretta Garzetta) and five species of birds terrestrial (Lalage sueurii, Linkmera lombokia, Nectarinia jugularis, Merops ornatus, and Zosterops palpebrosus) .Keywords: Birds, Mangroves, Gili Sulat, East Lombok